Efficacy of corifollitropin alfa followed by recombinant follicle-stimulating hormone in a gonadotropin-releasing hormone antagonist protocol for Korean women undergoing assisted reproduction - Park, Hyo Young (Clin Exp Reprod Med, 2015)
OBJECTIVE: To evaluate the effect of a gonadotropin-releasing hormone (GnRH) antagonist protocol using corifollitropin alfa in women undergoing assisted reproduction. METHODS: Six hundred and eighty-six in vitro fertilization-embryo transfer (IVF)/intracytoplasmic sperm injection (ICSI) cycles were analyzed. In 113 cycles, folliculogenesis was induced with corifollitropin alfa and recombinant follicle stimulating hormone (rFSH), and premature luteinizing hormone (LH) surges were prevented with a GnRH antagonist. In the control group (573 cycles), premature LH surges were prevented with GnRH agonist injection from the midluteal phase of the preceding cycle, and ovarian stimulation was started with rFSH. The treatment duration, quality of oocytes and embryos, number of embryo transfer (ET) cancelled cycles, risk of ovarian hyperstimulation syndrome (OHSS), and the chemical pregnancy rate were evaluated in the two ovarian stimulation protocols. RESULTS: There were no significant differences in age and infertility factors between treatment groups. The treatment duration was shorter in the corifollitropin alfa group than in the control group. Although not statistically significant, the mean numbers of matured (86.8% vs. 85.1%) and fertilized oocytes (84.2% vs. 83.1%), good embryos (62.4% vs. 60.3%), and chemical pregnancy rates (47.2% vs. 46.8%) were slightly higher in the corifollitropin alfa group than in the control group. In contrast, rates of ET cancelled cycles and the OHSS risk were slightly lower in the corifollitropin alfa group (6.2% and 2.7%) than in the control group (8.2% and 3.5%), although these differences were also not statistically significant. CONCLUSION: Although no significant differences were observed, the use of corifollitropin alfa seems to offer some advantages to patients because of its short treatment duration, safety, lower ET cancellation rate and reduced risk of OHSS.